Optimal metal domain size for photocatalysis with hybrid semiconductor-metal nanorods - Ben-Shahar, Yuval; Scotognella, Francesco; Kriegel, Ilka; Moretti, Luca; Cerullo, Giulio; Rabani, Eran; Banin, Uri (Nature communications, 2016)
Semiconductor-metal hybrid nanostructures offer a highly controllable platform for light-induced charge separation, with direct relevance for their implementation in photocatalysis. Advances in the synthesis allow for control over the size, shape and morphology, providing tunability of the optical and electronic properties. A critical determining factor of the photocatalytic cycle is the metal domain characteristics and in particular its size, a subject that lacks deep understanding. Here, using a well-defined model system of cadmium sulfide-gold nanorods, we address the effect of the gold tip size on the photocatalytic function, including the charge transfer dynamics and hydrogen production efficiency. A combination of transient absorption, hydrogen evolution kinetics and theoretical modelling reveal a non-monotonic behaviour with size of the gold tip, leading to an optimal metal domain size for the most efficient photocatalysis. We show that this results from the size-dependent interplay of the metal domain charging, the relative band-alignments, and the resulting kinetics. The efficiency of photocatalysis on semiconductor-metal hybrid nanostructures can be influenced by myriad factors. Here, through both experimental and theoretical efforts, the authors elucidate the influence of metal domain size upon performance of such structures, allowing future rational design.